Comparative Study of the effects of a Synthetic Pessticide (Endocel) and Plant Extracts on litter Decomposition in a Theobroma cacao Linn.Plantation. - Sonaike, Tolulope Seun (Obafemi Awolowo University, 2019)
xi,61